2005
DOI: 10.1598/rt.58.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Fluency: Bridge Between Decoding and Reading Comprehension

Abstract: A deep, developmental construct and definition of fluency, in which fluency and reading comprehension have a reciprocal relationship, is explicated and contrasted with superficial approaches to that construct. The historical development of fluency is outlined, along with conclusions of the U.S. National Reading Panel, to explore why fluency has moved from being “the neglected aspect of reading” to a popular topic in the field. A practical, developmental instructional program based largely on the theoretical fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
234
0
45

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(314 citation statements)
references
References 10 publications
13
234
0
45
Order By: Relevance
“…The comparative merits of teaching fluency versus discussion of word meanings were tested with struggling primary-school readers; it was found students who had learned to recognize the words to the point of automaticity answered more comprehension questions than students who merely were instructed on individual word meanings (Tan and Nicholson 1997). This is why fluency is now considered a prerequisite for comprehension (Snow et al 1998;Pikulski and Chard 2005 (Goswami 1999). However, it was found that four one-hour sessions of word games in Israel significantly increased children's performance (Bentin and Leshem 1993).…”
Section: Chaptermentioning
confidence: 99%
“…The comparative merits of teaching fluency versus discussion of word meanings were tested with struggling primary-school readers; it was found students who had learned to recognize the words to the point of automaticity answered more comprehension questions than students who merely were instructed on individual word meanings (Tan and Nicholson 1997). This is why fluency is now considered a prerequisite for comprehension (Snow et al 1998;Pikulski and Chard 2005 (Goswami 1999). However, it was found that four one-hour sessions of word games in Israel significantly increased children's performance (Bentin and Leshem 1993).…”
Section: Chaptermentioning
confidence: 99%
“…A automatização da leitura permite que esta seja feita sem esforço, libertando recursos cognitivos e atencionais para a compreensão do texto e para a sua monitorização. (NATIO-NAL READING PANEL, 2000;VIANA, 2002;PIKULSKI;CHARD, 2005).…”
Section: A Fluência Em Leituraunclassified
“…The operational definition used in the current study refers to reading accuracy as the translation of printed words into a representation similar to oral language (Algozzine et al, 2008;Capraro, 2006;Carlson et al, 2013;HØIen-Tengesdal & TØNnessen, 2010;Hudson et al, 2011;Miller & Keenan, 2009;Padeliadu & Antoniou, 2013;Pikulski & Chard, 2005;Rautenberg, 2013;Suggate et al, 2014;Weiser, 2013).…”
Section: Reading Accuracymentioning
confidence: 99%
“…Constructing meaning from written language requires making a connection to oral language (Capraro, 2006;Padeliadu & Antoniou, 2013). A printed word must be connected to an individual's phonological memory for the word and be connected to the meaning of the word or it cannot be accurately decoded or understood (Pikulski & Chard, 2005). Reading the words at an adequate rate is highly related to comprehension.…”
Section: Reading Accuracymentioning
confidence: 99%
See 1 more Smart Citation